Proceedings of the Sixth International Conference on Technological Ecosystems for Enhancing Multiculturality 2018
DOI: 10.1145/3284179.3284226
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Study of Proof of Concept Practices and their Connection with Information Systems and Information Science

Abstract: In this study, we have identified that a Proof of Concept can be characterized as a research practice and instrument of knowledge creation, based on a set of activities that are applied to the study and understanding of certain objects by the actors involved. In Information Systems Development, we have characterized a Proof of Concept as a system that creates sociotechnical phenomena and, with the aim of understanding these phenomena, we use the Context Engineering approach. Context Engineering represents the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 31 publications
0
6
0
1
Order By: Relevance
“…Neto et al [24] revealed that PoC practices are largely under-researched in scientific literature. PoCs are means to demonstrate that a potential solution is functionally feasible [25].…”
Section: Proof-of-concept In Is Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Neto et al [24] revealed that PoC practices are largely under-researched in scientific literature. PoCs are means to demonstrate that a potential solution is functionally feasible [25].…”
Section: Proof-of-concept In Is Researchmentioning
confidence: 99%
“…From a different angle, PoC activities aim to broaden problem understanding and provide space for scientific activities to create new knowledge that informs further design decisions, hence contribute to the future feasibility of a solution [25]. In this paper, we adopt the definition proposed by Neto et al [24] and define a PoC as "an activity system […] in a socio-technical context, with the purpose of evaluation, understanding, validation and exploration, and with the aim of learning about technological artifacts and their phenomena under study by organizations and PoC practitioners" (p. 2).…”
Section: Proof-of-concept In Is Researchmentioning
confidence: 99%
“…We understand to a certain extent that reusability is desirable, not as an absolute and unquestionable truth in any context, but as a contributed experience for practitioners in the context of PoC to "reflect on" a past and try to understand if past experiences can be "connected" in the current knowledge flow in the PoC activity. In other words, a simple change in the context of PoC, for example, a different parameterization in the software tool for the I/O simulation or the average response time calculated for read and write operations, could provoke a change in the composition of the final results and increase the probability of the domino effect in the context of the PoC (Neto et al, 2018). Because those "results live Table 5.…”
Section: The Use Of the Average In Performance Experiments In The Context Of Pocmentioning
confidence: 99%
“…Corbett (2000, p. 292) highlighted the problems of interpretation, which inevitably arise in the process of design and use. Thus, we examine how the formation of the flow of knowledge occurs, which can influence organizational memory and organization members, with possible knock-on or domino effects (Neto et al, 2018). In other words, we reflect on whether the absence of knowledge in the development and execution of PoC by its practitioners can be based on attributions of meanings, that is, from a pre-understanding regarding the unveiling of reality (original world versus the PoC world) that confronts them.…”
Section: Introductionmentioning
confidence: 99%
“…Section 2 describes the theoretical foundation and design methodology of the guide, as well as its components. Section 3 proposes a method for its use and in Section 4 the execution of a proof of concept [Neto et al 2018] is detailed. Final considerations are outlined in Section 5.…”
Section: Introductionmentioning
confidence: 99%